Influence of Interval From Calving and Season on Follicular Development, Onset of Oestrus, Conception and Embryonic Mortality During Early Post Partum Period of Cross Bred Cows Under Humid Tropical Climate - Ibraheem Kutty , Cholakkal (The Indian Journal of Animal Reproduction, 2025)
Dairy cows suffer extreme physiological stress during the early stages of lactation depending on the milk yield and  climatic adversities, delaying post-partum (PP) fertility. The present study intended to assess the influence of interval  from calving and seasons on the resumption of PP fertility. Reproductive ultrasonography of eight early PP cows each  was performed every week and continued year-round replacing four cows every month. Details of ovarian structures,  oestrus detected, AI done, conception, and embryonic loss were analyzed for variations between weeks of early PP and  across seasons. A total of 381 ultrasonography (USG) checks revealed functionally active ovaries throughout the period  of study having tiny follicles, prominent antral follicles, and evidence of recent ovulation in 99.23%, 94.17%, and 64.56%  respectively. Functionally active follicles were highest during summer and lowest in post-summer (P
Keywords: Conception; Dairy Cow; Embryonic Loss; Ovarian Follicle; Thermal Stress